Influencers como medio de difusión y su impacto en la masificación de las fake news en la red social whatsapp, año 2022 - Palma Alcivar, Luis Fernando (2022)
Communication is always innovating according to advances in technology, over the years it has become one of the primary needs for human beings who need to stay in constant communication. This evolution also brings with it the emergence of new protagonists, more information that needs to be processed in order to be massified later. This project arises with the idea of publicizing the power of communication and its protagonists and the veracity of the information that we are transmitting to our community, groups of friends and family, through the WhatsApp social network. In the process of the project we will conduct surveys aimed at one of our main WhatsApp groups and contacts in our network. Obtaining a result that brings us closer to reality in how fake news or (false news) in which its protagonists are local or international influencers are spread. As an important result we have is that fake news is being used as instruments of disinformation and that it causes a high degree of alarm in these groups of this social network, since this information is not verified, it influences the viralization in the different digital platforms.